Respon Pertumbuhan Tanaman Jahe Merah (Zingiber Officinale Rosc) Terhadap Pemberian Pupuk Kandang Sapi dan Pupuk NPK - Lubis, Elli Afrida; Lisdayani, Lisdayani (UNIVERSITAS LABUHANBATU, 2024)
The prospects for the development of red ginger plants in Indonesia are still quite bright, especially for export, the traditional medicine industry, the food and beverage industry and cooking spices. Fresh red ginger in Indonesia is exported to various countries including the United States, Japan, Singapore and Pakistan. The red ginger plant (Zingiber officinale Rosc) is one of the important herbs. During its growth, from planting to production, it is definitely a ginger plant. has absorbed a number of food elements. Therefore, efforts are needed to maintain, increase and increase soil fertility, including by fertilizing. One of the determining factors is the use of cow manure and NPK fertilizer. The aim of this research is to determine the effect of using doses of cow manure and NPK fertilizer on the growth of red ginger plants (Zingiber officinale Rosc.). This research uses a Factorial Randomized Block Design (RAK). which consists of 2 (two) treatment factors. The first factor is the dose of cow manure (K) consisting of 4 levels, namely:= Control,= 75 tons/ha (2kg/plot),= 150 tons/ha (4kg/plot)), K3= 225 tons/ha (6kg /plot)). The second factor, namely the dose of NPK fertilizer (M), consists of 3 levels, namely: M0= Control, = 0.4 gr/plot, M2= 0.6 gr/plot, M3 = 0.8 gr/plot. Observed variables include Plant Height, Number leaves/sample, and number of saplings/sample. The results of the research on the dose of cow manure showed a very real influence on plant height, number of leaves and number of tillers in red ginger plants. NPK fertilizer doses that are too high have an impact on low plant height, number of leaves, and number of red ginger plant saplings Keywords: red ginger, cow manure, NPK